Pengembangan Sistem Pompa Air Otomatis Berbasis PLTS Off-Grid untuk Irigasi Sawah - Ar Rasyid Arumas; Mahendra Widyartono; Ayusta Lukita Wardani; Reza Rahmadian (Elposys: Jurnal Sistem Kelistrikan, 2026)
Conventional irrigation systems in rural agricultural areas are generally operated manually and rely on fossil-fuel-based pumps, resulting in high operational costs and low efficiency, particularly during the dry season. The objective of this research is to develop an autonomous irrigation system based on an off-grid photovoltaic power system that operates automatically according to water availability conditions. The proposed system utilizes a 250 Wp photovoltaic panel, a 12 V 200 Ah VRLA battery, an Arduino Uno microcontroller, float switch sensors for water level detection, and a LoRa-based communication module for security and remote monitoring. Field testing was conducted under actual operating conditions during five hours of effective solar irradiation by measuring photovoltaic output parameters (voltage, current, power, and energy), pump operating performance, automatic control response, and LoRa communication reliability. The photovoltaic system produced a total daily energy of 622.34 Wh under the test conditions. The water pump operated for approximately 2.5 hours with an actual power consumption of ±500 W. The automatic control system successfully operated according to water availability in the river and irrigation demand in the rice field. In addition, the LoRa-based security system successfully transmitted warning signals over a distance of 300 m without data loss. These results indicate that the proposed system operates reliably for automatic rice field irrigation and remote security monitoring; however, increasing the photovoltaic capacity is recommended to better satisfy the system’s daily energy demand.